Insights for Alzheimer's disease pharmacotherapy and current clinical trials. (October 2022) - Nascimento, A.L.C.S.; Fernandes, R.P.; Carvalho, A.C.S.; Frigieri, I.; Alves, R.C.; Chorilli, M.
Abstract: Over the years, the scientific community has sought improvements in the life quality of patients diagnosed with Alzheimer's disease (AD). Synaptic loss and neuronal death observed in the regions responsible for cognitive functions represent an irreversible progressive disease that is clinically characterized by impaired cognitive and functional abilities, along with behavioral symptoms. Currently, image and body fluid biomarkers can provide early dementia diagnostic, being it the best way to slow the disease's progression. The first signs of AD development are still complex, the existence of individual genetic and phenotypic characteristics about the disease makes it difficult to standardize studies on the subject. The answer seems to be related between Aβ and tau proteins. Aβ deposition in the medial parietal cortex appears to be the initial stage of AD, but it does not have a strong correlation with neurodegeneration. The strongest link between symptoms occurs with tau aggregation, which antecede Aβ deposits in the medial temporal lobe, however, the protein can be found in cognitively healthy older people. The answer to the question may lie in some catalytic effect between both proteins. Amid so many doubts, Aducanumab was approved, which raised controversies and results intense debate in the scientific field. Abnormal singling of some blood biomarkers produced by adipocytes under high lipogenesis, such as TNFα, leptin, and interleukin-6, demonstrate to be linked to neuroinflammation worsens, diabetes, and also severe cases of COVID-19, howsoever, under higher lipolysis, seem to have therapeutic anti-inflammatory effects in the brain, which has increasingly contributed to the understanding of AD. In addition, the relationship of severe clinical complications caused by Sars-CoV-2 viral infection and AD, go beyond the term "risk group" and may be related to the development of dementia long-term. Thus, this review summarized the current emerging pharmacotherapies, alternative treatments, and nanotechnology applied in clinical trials, discussing relevant points that may contribute to a more accurate look. Highlights: Relationship between biomarkers, obesity, and COVID-19. 2021 clinical trials targeting Amyloid-β and Tau drugs. Alternative treatments based on non-drug therapy. Challenges of drug delivery systems (DDS).